IDEOLOGI DALAM TEKS FACEBOOK: Kajian Analisis Wacana Kritis - Arwanto, Joko (Institut Agama Islam Negeri (IAIN) Metro, 2015)
The purpose of this mini-research was to determine the ideology in the text facebook through the study of critical discourse analysis. The focus of this research is a ‘pages text’ or a hypertext accessed and printed on July 7, 2011 from a facebook accounts. The research method used is a three- dimensional model Fairclough. This study concludes that the ideology of the text information that facebook offers more humane capitalism, not capitalism with an orthodox style. The participant who are in hypertext facebook have ideologies competing for space and given the dominance that the meaning can be negotiated.